An enhanced oxygen electrode catalyst by incorporating CoO/SnO2 nanoparticles in crumpled nitrogen-doped graphene in alkaline media. Issue 55 (23rd May 2016) - Ma, Xiu-Xiu; He, Xing-Quan
Abstract : An advanced and highly efficient oxygen electrode catalyst was fabricated by anchoring CoO/SnO2 nanocrystals on nitrogen-doped graphene. Abstract : To address issues concerning energy consumption and the environment, it is of great importance to design a highly efficient, durable and inexpensive oxygen electrode for energy storage and conversion devices. In this work, CoO/SnO2 nanoparticles were successfully incorporated in nitrogen-doped graphene by a facile method. The composite was of porous structure, and exhibited efficient bifunctional activity and outstanding stability towards both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). For ORR, the catalyst favored a direct four-electron-transfer pathway, and produced kinetic current density values close to those of Pt/C. In addition, for OER, it achieved a lower overpotential at a current density of 10 mA cm −2 and a smaller Tafel slope than RuO2 . What is more, the value of the potential difference Δ E (OER–ORR), a measure of the overall bifunctionality of the catalyst, was 0.72 V, comparable with the values for state-of-the-art nonprecious bifunctional catalysts. The remarkable bifunctional activity of the catalyst was mainly attributed to the synergistic effects between metal oxides and nitrogen-doped graphene.